Women's land title ownership and empowerment: Evidence from India - Harold Glenn A. Valera; Takashi Yamano; Ranjitha Puskur; Prakashan Chellattan Veettil; Ishika Gupta; Phoebe Ricarte; Rohini Ram Mohan (Asian Development Bank (ADB), 2018)
This paper examines how women's participation in family decision-making is affected by land rights in rural areas in India. The 2005 Hindu Succession Act was legislated to protect women's rights to an equal share in ancestral property, including land. Using a unique rural household survey from Eastern Uttar Pradesh, Bihar, Odisha, and West Bengal where female enumerators were employed to interview female participants, we find that only 3% of the 8,000 rural households randomly selected in those four states have their land registered under women's names. Controlling for the potential endogeneity of land title ownership, we find that women's land title ownership has positive effects on their participation in decisions about farming, livelihood, and household activities. Using state leveldisaggregated data, however, we find that the signs and magnitudes of the impacts differ across the four states whose social and economic norms are diverse.
Keywords: D63; Q15; 330; decision-making; gender; India; women's land rights